Seatbelt Sign as an Indication for Four-vessel Computed Tomography Angiogram of the Neck to Diagnose Blunt Carotid Artery and Other Cervical Vascular Injuries. Issue 10 (October 2013) - Dhillon, Ramandeep Singh; Barrios, Cristobal; Lau, Cecilia; Pham, Jacqueline; Bernal, Nicole; Kong, Allen; Lekawa, Michael; Dolich, Matthew
Computed tomography angiography (CTA) of the neck has become the most common modality for diagnosing blunt carotid artery injury (BCAI). The protocol at our institution includes CTA on trauma patients with a seatbelt sign. The purpose of this study is to evaluate whether a solitary seatbelt sign is an indication for CTA of the neck to diagnose BCAI. We conducted a retrospective review of patients from 2000 to 2010 who received CTAs as a result of a seatbelt sign performed at our Level I trauma center. Four hundred eighteen patients received CTAs based on the presence of a seatbelt sign. Two hundred twenty-six had skeletal injuries, obvious soft tissue injuries, and/or positive findings on imaging, including 11 positive vascular findings with two BCAIs found. Patients with noncarotid vascular injuries on CTA had a higher Injury Severity Score than patients with solitary seatbelt signs (11.4 ± 7.6 vs 3.4 ± 4.2, P < 0.01). The correlation between seatbelt sign and positive finding on CTA was weak ( r = 0.007). Patients with vascular findings on CTA also had obvious hard/soft tissue injuries and/or positive findings on standard trauma imaging. This suggests that a protocol for CTA of the neck for patients with a seatbelt sign can be reserved for those with associated injuries on physical examination and/or findings on standard trauma imaging.